2017
DOI: 10.1111/ajco.12817
|View full text |Cite
|
Sign up to set email alerts
|

Combined transcatheter arterial chemoembolization and radiofrequency ablation in single‐session for solitary hepatocellular carcinoma larger than 7 cm

Abstract: Aims: To evaluate technical feasibility and treatment results of combined transcatheter arterial chemoembolization (TACE) and radiofrequency ablation (RFA) in single-session for solitary hepatocellular carcinoma (HCC) larger than 7 cm in diameter. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The indication for TACE+RFA was based on previous studies . Briefly, the indication was HCC 2–7 cm in maximum diameter, or HCC with fewer than seven nodules, that could be detected by ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The indication for TACE+RFA was based on previous studies . Briefly, the indication was HCC 2–7 cm in maximum diameter, or HCC with fewer than seven nodules, that could be detected by ultrasonography.…”
Section: Methodsmentioning
confidence: 99%
“…The indication for TACE+RFA was based on previous studies. 16,26,27 Briefly, the indication was HCC 2-7 cm in maximum diameter, or HCC with fewer than seven nodules, that could be detected by ultrasonography. In addition, we enrolled HCC patients who refused hepatic resection, even though the HCC was within the indication of hepatic resection according to the evidence-based clinical practice guidelines for HCC of The Japan Society of Hepatology 25 or BCLC staging and treatment strategy.…”
Section: Treatment For Hccmentioning
confidence: 99%
“…The clinical variables included tumor factors and therapeutic alliance. Several reports had pointed out TACE combined with MWA was safe and effective in the treatment of large HCC lesions [30][31][32]. Furthermore, the convenience of using nomogram derived from pretreatment clinical variables to assess prognosis for individual patients with HCC before initiation of treatment may improve patient-physician communication, decision making and selection of patients for prospective clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, Zuo et al [27] reported that the control rates of large HCC were 100.0%, 92.4%, 87.9% and 70.1% at 1, 3, 6 and 12 months after TACE combined with RFA, respectively. Ke et al [28] reported on repeated radiofrequency ablation combined with TACE/TAE in solitary large HCC. The cumulative OS rates at 1, 2 and 3 years were Figure 4.…”
Section: Discussionmentioning
confidence: 99%